IMPROVING STUDENTS’SPEAKINGSKILL THROUGH QUESTIONING TECHNIQUES - Muhammad Ridwan Sulaiman; Chairil Anwar Korompot; Geminastiti Sakkir (International Journal of Business English and Communication, 2024)
The aim of this research is to determine whether questioning techniques are successful at improving speaking skill and to identify the factor that can make questioning techniques effective or ineffective. This study is a pre-experimental design with a pre- and post-test for a single group. This study conducted quantitative techniques, this study. A speaking exam was employed as a research instrument by the researcher. Students took pre-test and post-test speaking assessments as a method of gathering data. Class IXG of SMP 1 Enrekang is the study's sample. There was a substantial change between the speaking ability scores of the studnents from the pre-test and the post-test. It was the Sig. was 0.000 0.05 (t = -9.635, p = 0.0005). Because the significant value (0.000) is less than the significant level, the statement there is a significant difference in the results of students who get questioning techniques treatments is accepted (0.05). It was concluded significantly different. Since H0 was rejected in this comparison and H1 was approved, it may be concluded that there is a significant difference in the effects of the questioning strategies on the development of students' speaking skills. The factors make questioning techniques effective are: they keep all student actively, they provide wait time, the question’s instruction is clearly, and The giving feedback of the students’ answer provide best response.